Design a Concept of Electrical Energy Regeneration from Conventional Lathe Based on Workload Analysis - Mohd Khairul Apnadi, Ahmad Syukran; Ibrahim, Badaruddin; Mustafa, Mohamad Zaid; Basri, Filza Izzati (Research and Innovation in Technical and Vocational Education and Training, 2024)
To reduce excessive power consumption, this study developed a conceptual design for power generation based on the movement of the machine motor during machining processes. The objective of this study is to develop the concept design of energy recovery from conventional lathes while determining the effects of conventional lathe load through five basic machining activities. The researcher conducted the study methodically by creating the conceptual design by the phases defined in the research methodology, which refers to the Analysis Process Model to achieve the objective of this study. According to the study conducted, electricity can be generated with the right calculation technique and equipment, including generators, solar inverters, and batteries. In conclusion, the objectives have been achieved in creating the design concept for power generation from conventional lathes under the influence of machining load.